Resectability, Resections, Survival Outcomes, and Quality of Life in Older Adult Patients with Metastatic Colorectal Cancer (the RAXO-Study) - Lehtomäki Kaisa; Soveri Leena-Maija; Osterlund Emerik; Lamminmäki Annamarja; Uutela Aki; Heervä Eetu; Halonen Päivi; Stedt Hanna; Aho Sonja; Muhonen Timo; Ålgars Annika; Salminen Tapio; et al. (MDPI, 2025)
Older adults are underrepresented in metastatic colorectal cancer (mCRC) studies and thus may not receive optimal treatment, especially not metastasectomies. The prospective Finnish real-life RAXO-study included 1086 any organ mCRC patients. We assessed repeated centralized resectability, overall survival (OS), and quality of life (QoL) using 15D and EORTC QLQ-C30/CR29. Older adults (>75 years; n = 181, 17%) had worse ECOG performance status than adults (<75 years, n = 905, 83%), and their metastases were less likely upfront resectable. The local hospitals underestimated resectability in 48% of older adults and in 34% of adults compared with the centralized multidisciplinary team (MDT) evaluation (p < 0.001). The older adults compared with adults were less likely to undergo curative-intent R0/1-resection (19% vs. 32%), but when resection was achieved, OS was not significantly different (HR 1.54 [CI 95% 0.9-2.6]; 5-year OS-rate 58% vs. 67%). 'Systemic therapy only' patients had no age-related survival differences. QoL was similar in older adults and adults during curative treatment phase (15D 0.882-0.959/0.872-0.907 [scale 0-1]; GHS 62-94/68-79 [scale 0-100], respectively). Complete curative-intent resection of mCRC leads to excellent survival and QoL even in older adults. Older adults with mCRC should be actively evaluated by a specialized MDT and offered surgical or local ablative treatment whenever possible.